Managing Your Outsourced IT Services Provider How to Unleash the Full Potential of Your Global Workforce - Upadrista, Venkatesh; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Managing Your Outsourced IT Services Provider teaches executives and managers of organizations how to unleash the full potential of their outsourced IT services workforce and IT-enabled business processes safely and profitably. Drawing on two decades of experience managing client relationships for global IT services companies, Venkatesh Upadrista guides outsourcing organizations around the hazards of geographic distance, linguistic miscommunication, organizational mismatch, and functional disparity between receiver requirements and provider capabilities. The first half of the book describes what an outsourcing organization needs to know about the IT services providers industry in general to deal intelligently with specific providers: namely, the industry’s organizational types, strategic drivers, competitive labor market constraints, and tactics for hitting P&L targets. The second half of the book teaches outsourcers how to evaluate prospective providers, craft service level agreements, formalize best practices, and manage the full gamut of receiver─provider relationships to optimize outcome in terms of cost, timeliness, and quality of services received. The descriptions and prescriptions in Managing Your Outsourced IT Services Provider apply equally to onshore and offshore outsourcing, but examples and case studies focus on offshoring. In addition, Upadrista analyzes the advantages, disadvantages, and special considerations and caveats of single provider outsourcing and captive centers.
Keywords: Business; Management science; Computers; Business and Management, general; Information Systems and Communication Service